"Reprende […] onde o merece o vício": A sátira na poesia do Classicismo e do Maneirismo. Issue 1 (2nd January 2018) - Nogueira, Carlos
ABSTRACT: If, deluded by general literary history, we only value what is ethical and responsible in classical Portuguese satire, forgetting that it can also contain individual arbitrariness aimed at the destruction of an object, we will miss the moments when, as in medieval satire, the factor of constitution seems to be the ruthless and immoral personalization of criticism of persons, institutions, or entities. The aesthetics of moderation ends up promoting a subtly saturated and concrete language that seems to pursue the annulment of the other rather than a corrective social function. In Mannerism we find the most aesthetically elaborate examples of satire that challenges destiny or God in relation to the evils that fall upon an impotent but insubstantial self before such sensitive questions of metaphysical morality, a satire whose classic style gives it an aesthetic dignity and textual model without exception. In this article, we will see the different paths of classic and Mannerist satire, using the works of poets such as Sá de Miranda, António Ferreira, Pêro de Andrade Caminha, André Falcão de Resende, and Fernão Rodrigues Lobo Soropita.